Five auditions based on the use of music as therapy (Mayéutica Revista Científica de Humanidades y Artes, 2021)
I remember well, almost from memory, a fragment contained in the first lines from the book The Music of Man by Yehudi Menuhin and Curt Davis, as I profoundly impacted my years of study at the Central University of Venezuela: ¨The cry of the newborn affirms its new independence and a premonition of responsibility and hope¨. This assertion was supported by the fact that at the moment of birth, the protection of the mother's womb is abandoned with its volume of sounds, particularly the heart, while estimating a haunting greetings for the future. They concluded that this cry is a song to life and they understood music as the first form of expression of the human being. It is interesting given that some research conferred that primacy on pictographs, a drawn figure or series of them, with meaning. Thus, they carryreason the aforementioned authors: the first existential cry is a sound that express and transmit, definitely. It is our communicative antecedent initial. In any case, in the arts is the germ of language, now spoken now written.